Kolase Edukatif: Strategi Pemanfaatan Media Kolase Dalam Mengembangkan Minat Belajar Anak - Ariani, Nyoman Wiraadi Tria; Dewi, Putu Ayu Septiari; Sukriani, Ni Luh; Sukasih, Ni Kadek Intan (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
The essence of early childhood education is to motivate children so that their potential can develop optimally. Learning is aimed at mastering basic knowledge and skills and fostering expression, attitudes, and the child's interest in learning. The child's learning interest can be influenced by internal and external factors, such as encouragement from within the child and the surrounding environment. One of the issues in early childhood learning is the lack of learning interest, which can be caused by internal and external factors. Learning interest, as an individual's inclination towards something desirable, has a significant impact on a child's learning achievement. Therefore, it is important to create an enjoyable learning environment that stimulates the child's interest. Collage media is one form of learning activity that can enhance creativity and learning interest in children. Collage activities allow children to express themselves creatively by combining various materials, such as paper, fabric, colors, and shapes. The creativity of children can be developed from an early age, and this creativity can help them overcome various challenges in life. This research adopts the Classroom Action Research (CAR) approach with 25 students from TK A Pratama Widya Pasraman Adnyani as research subjects. Through continuous actions, the use of collage media successfully increased the children's learning interest significantly. The research results indicate that children showed a positive response to college activities, and their learning interest increased significantly after the implementation of actions.